Effectiveness of teaching physical education to learners with multiple disabilities in the Highglen district in Harare, Zimbabwe - Liana Musekiwa (International Journal of Studies in Psychology, 2025)
This study explored the effectiveness of teaching physical education to learners with multiple disabilities in two special schools in the Highglen district. The study employed a qualitative approach rooted in an interpretative research paradigm. A case study was used as a research design. Semi-structured interviews, lesson observations, and focus group discussions were used as data collection tools. Twenty participants were selected using purposive sampling from two special schools in the Highglen district, Zimbabwe. Data were analysed using content thematic analysis to identify key themes. Results showed different factors affecting the effective teaching of Physical Education to learners with multiple disabilities. These include health issues, lack of support from different stakeholders, teachers' attitudes towards learners with multiple disabilities, lack of skills and knowledge, learners' attitudes toward PE, shortage of appropriate PE equipment, and the school environment. The study gave some recommendations, including holding campaigns by respective education ministries that may help correct attitudes in school heads, teachers, parents, and learners. Schools should be assisted in acquiring resources and equipment to ease the teachers' work. Teachers ' professional development should be prioritised to equip them with the necessary skills and knowledge.